Urogenital dysfunction in patients after miniinvasive restorative low anterior resection with total mesorectal excision - Macháčková, Mária; Škrovina, Matej; Szikhart, Mário; Martínek, Lubomír; Benčurik, Vladimír; Bartoš, Jiří; Dosoudil, Michal (Wideochirurgia i Inne Techniki Mało Inwazyjne, 2022)
INTRODUCTION: Over the last decades outcomes for rectal cancer surgery have improved, with increasing survival rates. Nevertheless, functional disorders are still frequent. AIM: To evaluate sexual and urinary outcomes of miniinvasive total mesorectal excision (TME). MATERIAL AND METHODS: Between March 2016 and June 2018 patients with rectal cancer who underwent miniinvasive TME with a sphincter-saving procedure were enrolled. The questionnaires were completed before therapy, and 6, 12, and 24 months after stoma closure. We used the Female Sexual Function Index (FSFI), the International Prostate Symptom Score (IPSS) and the International Index of Erectile Function questionnaire (IIEF). RESULTS: Ninety-eight patients completed the questionnaires. Only patients who underwent laparoscopic (39) or robotic TME (27) were enrolled. The characteristics and surgical outcomes did not differ significantly between these groups. The IPSS between the groups was comparable before and after the operation with no significant difference, increased at 6 months and then decreased consecutively. In comparison with baseline, IPSS was significantly lower in the laparoscopic and robotic groups at 6 months and was comparable to baseline at 24 months in both groups. Oppositely, the IIEF was significantly lower at 6 months after ileostomy closure in the robotic group (p < 0.05), but not in the laparoscopic group (p = 0.59) and both returned to baseline at 24 months. FSFI was significantly lower in the laparoscopic group (p = 0.017) 6 months after surgery and returned to baseline at 24 months in both groups. CONCLUSIONS: Laparoscopic and robotic TME showed similar functional results 2 years after stoma resection.